A Clinical and Ultrasonographic Study of Risk Factors for Elbow Injury in Young Baseball Players. (April 2016) - Tajika, Tsuyoshi; Kobayashi, Tsutomu; Yamamoto, Atsushi; Kaneko, Tetsuya; Shitara, Hitoshi; Shimoyama, Daisuke; Iizuka, Yoichi; Okamura, Koichi; Yonemoto, Yukio; Warita, Toshiro; Ohsawa, Takashi; Nakajima, Ichiro; et al.
Purpose: To determine the risk factors for elbow injury and its association with glenohumeral internal rotation deficit among young baseball players. Methods: 229 baseball players aged 9 to 14 (mean, 11) years completed a self-administered questionnaire with items related to years of playing baseball, hours of training per weekday, days of training per week, and past and present experience of elbow pain. Two orthopaedic surgeons measured the range of motion of both shoulders and elbows. Another 2 orthopaedic surgeons performed ultrasonography to detect any elbow abnormality such as fragmentation of the medial epicondylar apophysis and osteochondritis dissecans of the capitellum. Using univariate and multivariable analyses, participants with or without elbow abnormality were compared to determine the risk factors for elbow abnormality. Results: Elbow abnormality was detected in 100 of the participants and comprised osteochondritis dissecans of the capitellum (n=18) and fragmentation of the medial epicondylar apophysis (n=82). Elbow abnormality was associated with being a pitcher, past and present experience of elbow pain, loss of elbow extension, and the side-to-side internal rotation difference. The 100 participants with elbow abnormality were stratified into symptomatic (n=57) or asymptomatic (n=43) of elbow pain. Those with elbow abnormality and elbow pain was associated with being a pitcher. Conclusion: Being a pitcher was a risk factor for both elbow abnormality and elbow pain. Nonetheless, 43% of baseball players with elbow abnormality were asymptomatic. The use of ultrasonography was effective in detecting elbow abnormality and enabling early treatment.